Front Cover: Spatially Resolved Electron Transport through Anode‐Respiring Geobacter sulfurreducens Biofilms: Controls and Constraints (ChemElectroChem 10/2021). Issue 10 (19th April 2021) - He, Xiaojia; Chadwick, Grayson; Jiménez Otero, Fernanda; Orphan, Victoria; Meile, Christof
Abstract : The Front Cover shows characteristic images of G. sulfurreducens biofilms on the anode surface (gray), the distribution of anabolic activity (yellow=high, blue=low), and the equation central to the description of electron transfer and simulated activity profiles. More information can be found in the Article by X. He et al .